If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -1.60x + b Reorder the terms: y = b + -1.60x Solving y = b + -1.60x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = b + -1.60x
| -9x^2+35x-30=1-x | | 4y-0.9=5y | | 9(x+5)=6x+2 | | (2+y)(3y+7)=0 | | -3(-5x+2)= | | (8x+1)2+5=10 | | 3x^4+33x^3+90x^2=0 | | -5(4x-2)= | | a^(1/3)*a^(4/3) | | 4x-7x-13=-3x+7-13 | | (6x+2)(3x-5)=(9x-4)(2x+4) | | p^2p/p^-5 | | 2/3x-1=-1/3x-5 | | (2x^4+6y)(2x^4-6y)= | | 2(3x+3)=5(x-4) | | -3(x+5)=2-2x | | 12x^2+4x+15=0 | | 3(7r-12)=21r-6 | | 63+30t+3t^2=0 | | 4x+2.9=9.7 | | 7(x+1)=-2(x-4)+x | | 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 |